A universal method for constructing stretchable and conductive connections in flexible electronics - Yahui Zhao; Qiyang Ruan; Tongtong Li; Hongyun Qiu; Ruipeng Zhang; Shuai Wen; Lifeng Chi; Shaobo Ji (npj Flexible Electronics)
Abstract Integrating stretchable and rigid electric units presents a significant challenge in manufacturing stretchable electronics. Their surface property differences prevented reliable stretching-tolerant connections. Here, we report a universal method to construct stretchable connections based on interfacial covalent reactions. It enables robust and conductive bonding among various soft/rigid electronics through simple surface modification and interfacial reaction. The bonding between SEBS rubber and metals reached stretchability over 250% with interfacial toughness over 200 N/m. The ultrathin connection layer provided conductive pathways, achieving an electrical stretchability of 60% between Au-deposited SEBS and Cu sheets. Connections between liquid metal-based stretchable conductors could withstand more than 10,000 stretching cycles to 60% strain while maintaining their high conductivity. The versatility and stability of this method were further proved by fabricating electronic devices that integrated soft and rigid units, including circuits on papers and a gesture-visualizing glove with LEDs, highlighting the robustness of the stretchable connections.